High serum glial fibrillary acidic protein levels are associated with increased risk of post-stroke cognitive impairment - Shan, Wanying; Jiang, Rui; Wang, Jing; Xu, Guoli; Zhao, Jie; Zhai, Guojie; Shao, Jiaxin (Frontiers in Aging Neuroscience, 2025)
Background and purposeThe correlation between glial fibrillary acidic protein (GFAP) and cognitive impairment in acute ischemic stroke patients remains uncertain. We aimed to evaluate GFAP in serum as predictor of post-stroke cognitive impairment (PSCI) at 90 days.MethodsFrom March 2022 to February 2023, patients with first-ever ischemic stroke were prospectively enrolled. Serum GFAP concentrations were measured within 24 h after admission using an enzyme-linked immunosorbent assay. Cognitive function measurement was performed at the 90 days follow-up using the Mini-mental state examination (MMSE). A MMSE score <27 was defined as PSCI. Multiple logistic regression and restricted cubic spline were performed to examine the association between GFAP and cognitive impairment.ResultsA total of 336 patients (mean age: 66.3 ± 9.0 years; 58.3% male) with acute ischemic stroke were included. The median GFAP levels were 0.73 ng/mL (interquartile range, 0.38–1.09 ng/mL). During the 3-month follow-up, 164 participants (48.8%) experienced PSCI. Higher GFAP levels were independently associated with PSCI after adjusting for potential confounders (per 1-unit increase, odds ratio: 3.91; 95% confidence interval: 2.24–6.82; p = 0.001). Additionally, restricted cubic spline confirmed a linear relationship between serum GFAP concentrations and PSCI risk (P for linearity = 0.001).ConclusionThis study demonstrated that higher levels of GFAP were associated with PSCI, suggesting that GFAP could be a promising and straightforward screening indicator of cognitive impairment after stroke.